The Role of Michał Ćwirko-Godycki (1901-1980) in Formation of Anthropology of Sports - Drozdrowski, Zbigniew (Anthropological Review, 1983)
Despite earlier traditions, full development of anthropology applications to physical education and sports begun with foundation of the Chair of Physical Education at the University of Poznań in 1819 where, among other disciplines. anthropology: was taught and anthropological research conducted. In the process of development of anthropology in the academic centre of physical education a great role was played by the late Michał Ćwirko-Godycki. His contribution to the subdiscipline may be summarized as follows: 1. his own research on development of schoolchildren supplied information on influence of various factors, among them physical exorcises, on the development, 2. he inspired and supervised research of many students that explained morphological conditioning of physical exercises and their impact on morphology, contributed to the knowledge of chronobiology (biorythms) and to the theory of result in sports, ‘that constitutes a large part of what is now called the anthropology of sports, and 3. he has organized a special anthropology department and editorial facilities to promote the subdiscipline. A number of persons now active in all sorts of institutions related to physical education and sports were his students. Now they have introduced elements of anthropology into research on physical education, sports, tourism and recreation and rehabilitation of convalescents and invalids.